PELESTARIAN PENDIDIKAN KELUARGA DALAM KONTEKS PEMIKIRAN ISLAM - bin yahya lizam, miskahuddin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2023)
ABSTRACTEducation based on Islamic teachings in Muslim families is a major factor that is very important to be preserved as early as possible well and perfectly. Mainly the preservation of education in a family is to be able to form the character of the firmness of faith and charity in the independence and mental resilience for the life of the Muslim family in the face of various problems trials and challenges of life globally. Teaching materials in Islamic education are many kinds such as aqidah education, morals and practices of worship both mandatory and sunnah of various other Islamic values contained in the teachings of Islam are easy and may be learned correctly and correctly. The preservation of family education itself can include a universal and comprehensive meaning in the form of supervision and self-management efforts in a family that is intact with the values of Islamic teachings to organize a perfect and stable life in a way Islam is beautiful and peaceful as through a variety of positive activities that are beneficial in the guidance of a healthy religion to the safety of life and happiness born and inner as well as safety and happiness in the world and in the hereafter later. Therefore protection, protection, harmonious family supervision and self-preservation with the values of Islamic teachings in the family through reviving the atmosphere of Islamic education in a family is a true inevitability that must be done all family members in various ways in order to stay sustainable based on the education of good and quality religious normality so as to realize the use of the right time as carefully as possible to develop, develop, animate or promote the teachings of Islam with selective and continuous in his family so as to build or animate a harmonious atmosphere based on the values of Islamic teachings in the household or family to remain shady and shining to answer or face various problems and tests of life in the social dynamics of the challenges of the times with an effort to prepare and build generations of resilient and qualified nations in the midst of a global era life. Pendidikan berbasis ajaran Islam dalam keluarga muslim merupakan faktor utama yang amat penting untuk dilestarikannya sedini mungkin secara baik dan sempurna. Utamanya pelestarian pendidikan itu  dalam sebuah keluarga adalah akan dapat membentuk karakter keteguhan iman dan amal shalih dalam kemandirian dan ketahanan mental bagi kehidupan keluarga muslim tersebut dalam menghadapi berbagai problem cobaan dan tantangan hidup secara global. Materi-materi ajar dalam pendidikan Islam itu banyak macamnya misalnya berupa pendidikan aqidah, akhlak dan praktik ibadah baik yang wajib maupun yang sunnah dari berbagai tata nilai keislaman lainnya yang terkandung dalam ajaran agama Islam yang mudah dan mungkin dipelajarinya dengan tepat dan benar. Pelestarian pendidikan keluarga itu sendiri bisa mencakup makna yang universal dan komprehensif berupa upaya pengawasan dan pengelolaan diri dalam keluarga yang utuh dengan nilai-nilai ajaran Islam untuk menata hidup sempurna dan stabil dengan cara Islam yang indah dan damai seperti melalui berbagai kegiatan positif yang bermanfaat dalam tuntunan agama yang sehat guna menuju keselamatan hidup maupun kebahagiaan lahir dan batin juga keselamatan dan kebahagian di dunia maupun di akhirat kelak. Oleh karena itu proteksi perlindungan, pengawasan keluarga harmonis dan pemelihara diri dengan nilai-nilai ajaran Islam dalam keluarga lewat menghidupkan suasana pendidikan Islam dalam sebuah keluarga adalah merupakan keniscayaan sejati yang mesti dilakukannya semua anggota keluarga dengan berbagai cara agar tetap lestari berdasarkan pendidikan normalitas agama yang baik dan bermutu sehingga mampu mewujudkan pemamfaatan waktu yang tepat secermat mungkin guna mengembangkan, menghidupkan atau pun memajukan ajaran agama Islam dengan selektif dan berkesinambungan dalam keluarganya sehingga mampu membangun atau menghidupkan suasana harmonis berdasarkan nilai-nilai ajaran Islam dalam rumah tangga atau keluarga agar tetap teduh dan bersinar guna menjawab atau menghadapi berbagai problem dan ujian hidup dalam dinamika sosial tantangan zaman dengan upaya mempersiapkan maupun membangun generasi-generasi bangsa yang tangguh dan berkualitas ditengah-tengah kehidupan zaman yang global.